Clinical Profile of Stroke Patients Attended in a Tertiary Care Hospital- Study of 219 cases - Anwar, Nayeem; Khan, Md Rezaul Karim; Anwar, Nawreen Binte; Nahar, Shamsun; Md Shahidullah, - (Bangladesh Journal of Neuroscience, 2016)
Background: Stroke is serious pathology with a immense impact on the functional and vital prognosis. It is the leading cause of death worldwide. The objective of the study was to observe clinical profile of stroke patients and important risk factors. Methods: It was a cross-sectional descriptive study conducted in the department of Neurology, BangabandhuSheikh Mujib Medical Universiy(BSMMU), Shahbag, Dhaka from August 2014 to November2015. All patients above 18 years of age and both sexes attending the above mentioned department meeting all inclusion and exclusion criterias and confirmed CT/MRI scan of Brain were included in this study. Results: A total of 219 patients were studied. Maximum 93(42.5%) patients were in age group of 61-70 years followed by 51(23.3%) and 30(13.7%), in the age group of 51-60 years and 71-80 years respectively. Male 138(63%) were predominant than female 81(63%). 78(35.61%) patients had weakness in both sides of the body, 66(30.1%) had weakness in the left side and 36(16.4%) had weakness in the right side of the body. 190 (87.7) patients had ischemic stroke and 29(12.3%) had hemorrhagic stroke. Among risk factors dyslipidemia was in 185(84.5%) patients, hypertension, smoking habits, diabetes mellitus and ischemic heart disease were present in 165(75.3%), 120(54.8%), 105(47.9%) and 42 (19.2%) patients respectively. H/O recurrent stroke was present in 55(25%) cases. Conclusion: Stroke cases were male predominant where dyslipidaemia was the most common risk factor, most common type of stroke was ischemic, most common presentation was hemiplegia/monoplegia and commonest age of presentation was seventh decade. Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 16-20